Cardiovascular risk in patients with small and medium abdominal aortic aneurysms, and no history of cardiovascular disease. Issue 10 (26th June 2014) - Sohrabi, S.; Wheatcroft, S.; Barth, J. H.; Bailey, M. A.; Johnson, A.; Bridge, K.; Griffin, K.; Baxter, P. D.; Scott, D. J. A.
<x xml:space="preserve">Abstract</x> Background Cardiovascular disease (CVD) is the main cause of death in people with abdominal aortic aneurysm (AAA). There is little evidence that screening for AAA reduces all‐cause or cardiovascular mortality. The aim of the study was to assess whether subjects with a small or medium AAA (3·0–5·4 cm), without previous history of clinical CVD, had raised levels of CVD biomarkers or increased total mortality. Methods This prospective study included subjects with a small or medium AAA and controls, all without a history of clinical CVD. CVD biomarkers (high‐sensitivity C‐reactive protein, hs‐CRP; heart‐type fatty acid‐binding protein, H‐FABP) were measured, and survival was recorded. Results Of a total of 815 people, 476 with an AAA and 339 controls, a cohort of 86 with small or medium AAA (3–5·4 cm) and 158 controls, all with no clinical history of CVD, were identified. The groups were matched for age and sex. The AAA group had higher median (i.q.r.) levels of hs‐CRP (2·8 (1·2–6·0) versus 1·3 (0·5–3·5) mg/l; P < 0·001) and H‐FABP (4·6 (3·5–6·0) versus 4·0 (3·3–5·1) µg/l; P = 0·011) than controls. Smoking was more common in the AAA group; however, hs‐CRP and H‐FABP levels were not related to smoking. Mean survival was lower in the AAA group: 6·3 (95 per cent confidence interval (c·i.) 5·6 to 6·9) years versus 8·0 (7·6 to 8·1) years in controls (P < 0·001). Adjusted mortality was higher in the AAA group (hazard ratio 3·41, 95 per cent c·i. 2·11 to 9·19; P < 0·001). Conclusion People with small or medium AAA and no clinical symptoms of CVD have higher levels of hs‐CRP and H‐FABP, and higher mortality compared with controls. They should continue to receive secondary prevention against CVD.